The Domino's boogergate incident - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
In April 2009, two Domino's Pizza employees posted a video on YouTube showing one of the employees sticking cheese up his nose and then putting it in a sandwich. This case describes how Domino's handled the public relations crisis.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). The Domino's Boogergate Incident. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 195-197). Los Angeles: ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Domino's Pizza (Firm); Public relations -- Case studies; Crisis management -- Case studies; Fast food restaurants -- Public relations -- Case studies